2018
DOI: 10.1002/cjce.23297
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of growth kinetics of Debaryomyces hansenii (LAF‐3 10 U) in petroleum refinery desalter effluent

Abstract: Desalter effluent is a difficult to treat wastewater stream emerging from petroleum refining operations. In this study, an osmotolerant and halotolerant yeast, Debaryomyces hansenii, was investigated for the first time for its use in removing phenol from simulated and actual desalter effluent. D. hansenii was able to degrade phenols at substrate COD concentrations ranging from 300–1200 mg L−1, whereas the substrate inhibition was noted as COD increased from 2000–4000 mg L−1. Three kinetic models (Andrews, Aiba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The SDE in 1 L distilled water was prepared as described in Table 1. The amount of NaCl in Imperial Oil DE from Sarnia, ON, was measured by Maxam Laboratories at 1000 mg L −1 (Azimian et al, 2019); therefore, the same salt concentration was used in the SDE. The pH of all growth media was adjusted to range between 6 and 6.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SDE in 1 L distilled water was prepared as described in Table 1. The amount of NaCl in Imperial Oil DE from Sarnia, ON, was measured by Maxam Laboratories at 1000 mg L −1 (Azimian et al, 2019); therefore, the same salt concentration was used in the SDE. The pH of all growth media was adjusted to range between 6 and 6.5.…”
Section: Methodsmentioning
confidence: 99%
“…D. hansenii is found in salty foods, blue cheese, nd brines, and it has both high respiratory and low fermentative activity (Calahorra et al, 2009; Şahin, 2017). This yeast was previously shown to remove phenols (aromatic compounds) (Azimian et al, 2019) and dodecane (an n‐alkane hydrocarbon) (García‐Lugo et al, 2018). Previous studies have shown that high substrate concentrations are inhibitory for yeast cultivation; therefore, continuous cultivation at a steady state in a continuous stirred‐tank reactor (CSTR) may be an effective way to control specific growth rates and avoid substrate inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition arising from osmosensitivity can be one such phenomenon and is further addressed in this paper. This modeling of quantitative description of substrate inhibition and inhibition due to a high degree of osmotic stress have previously been studied using different types of growth kinetic equations (Azimian et al, 2019;Ciranna et al, 2014;Dötsch et al, 2008;van Niel et al, 2003). A non-competitive equation is commonly used to describe growth inhibition due to substrate or soluble end products (Ciranna et al, 2014;van Niel et al, 2003).…”
Section: Although a Promising Candidate For Industrial Biohydrogen Prmentioning
confidence: 99%
“…However, substantial dilution is required for conventional wastewater treatment due to the presence of salt, heavy metals, and other toxic compounds. [ 7 ] Petroleum refineries usually leave a high concentration of oil, in both miscible and immiscible forms, in the effluent. [ 8 ] Hence, different separation technologies have been developed to treat petroleum effluent; nevertheless, petroleum wastewater, after using primary and conventional separation technology, does not meet environmental limits.…”
Section: Introductionmentioning
confidence: 99%